Strategi Coping Pernikahan Pada Suami Anggota Jamaah Tabligh - Anggraita, Sukma Fajar, Setiyo Purwanto, S.Psi.,M.Si, Psi (2016)
As a member of Tablighi Jamaat, are required to be active in khuruj activity. But the role as husband and head of the family should go hand in hand. However, if one less role goes well it would appear the problem. These problems are likely to affect the other role. This is where the need for appropriate coping strategies in an active husband Tablighi Jamaat, so that later in their daily walk selarastanpa can cause permsalahan. The purpose of this research is to know, understand and describe the coping behaviors of members carry out missionary husband. The research questions include three things: What is the orientation of the individual in determining the wedding couple Tablighi Jamaat? Which additional problems faced by members of Jamaah Tabligh husband? How do behavioral coping husband who was an active member of Jamaah Tabligh ?. This study uses a qualitative method by interview and observation. Methods of data analysis using descriptive analysis, data collection using purposive sampling method. Researchers chose informant number three criteria are married, and is active in Tablighi Jamaat with the minimum requirement has been Khuruj for forty days. These results indicate that a husband who is active in Tabligh Jamaat in general has made coping well and understand how to resolve the problems being faced in particular by receiving as a learning problem . Not responding to problems with emotions , making the planning of the problems faced. Environmental as well as social support from family and Tablighi Jamaat especially where informants can discuss issues with people who can be trusted by him . issues resolved through the process of screening and consideration